1999
DOI: 10.1172/jci4876
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte chemoattractant protein-1 promotes macrophage-mediated tubular injury, but not glomerular injury, in nephrotoxic serum nephritis

Abstract: Monocyte chemoattractant protein-1 (MCP-1) is upregulated in renal parenchymal cells during kidney disease. To investigate whether MCP-1 promotes tubular and/or glomerular injury, we induced nephrotoxic serum nephritis (NSN) in MCP-1 genetically deficient mice. Mice were analyzed when tubules and glomeruli were severely damaged in the MCP-1-intact strain (day 7). MCP-1 transcripts increased fivefold in MCP-1-intact mice. MCP-1 was predominantly localized within cortical tubules (90%), and most cortical tubules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
197
3
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(218 citation statements)
references
References 41 publications
16
197
3
2
Order By: Relevance
“…Furthermore, MCP-1 plays a role in hypertensive renal damage in the two-kidney one-clip rat model (31), which is possibly mediated by angiotensin II (32). Interestingly, MCP-1-deficient mice compared with wild-type mice exhibit no differences in glomerular lesions in nephrotic serum-induced nephritis, but exhibit less tubulointerstitial lesions (33). These reports support an important role of locally produced MCP-1 on the initiation and progression of renal damage, particularly tubulointerstitial damage.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, MCP-1 plays a role in hypertensive renal damage in the two-kidney one-clip rat model (31), which is possibly mediated by angiotensin II (32). Interestingly, MCP-1-deficient mice compared with wild-type mice exhibit no differences in glomerular lesions in nephrotic serum-induced nephritis, but exhibit less tubulointerstitial lesions (33). These reports support an important role of locally produced MCP-1 on the initiation and progression of renal damage, particularly tubulointerstitial damage.…”
Section: Discussionmentioning
confidence: 98%
“…Use of this experimental tool has been instrumental in demonstrating the potential pathogenic role of several mediators, including a variety of adhesion molecules, chemokines, and cytokines (23)(24)(25)(26)(27)(28)(29). Proteinuria is typically the first indicator that surfaces in both experimental and spontaneous immune nephritis (1)(2)(3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…MCP-1 is a chemokine which induces chemotaxis of monocytes/macrophages into an injured tissue, and is upregulated by, in part, TGF-b signaling. 53,54 Real-time RT-PCR showed that ectopic BMP-7 expression suppressed upregulation of mRNA expression of TGF-b1 and MCP-1 in healing, burned, corneas at both Days 10 and 20, whereas expression of VEGF mRNA was not reduced at Day 10 ( Figure 7a-c). Immunohistochemical staining in paraffin sections also showed that TGF-b1 and 2 were both expressed in the epithelium of the uninjured cornea (Figure 7d).…”
Section: Bmp-7-ad-treated Corneas Show Reduced Expression Of Growth Fmentioning
confidence: 99%